Handbook of Individual Differences in Cognition Attention, Memory, and Executive Control - Gruszka, Aleksandra; Matthews, Gerald; Szymura, Blazej; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
As cognitive models of behavior continue to evolve, the mechanics of cognitive exceptionality, with its range of individual variations in abilities and performance, remains a challenge to psychology. Reaching beyond the standard view of exceptional cognition equaling superior intelligence, the Handbook of Individual Differences in Cognition examines the latest findings from psychobiology, cognitive psychology, and neuroscience, for a comprehensive state-of-the-art volume. Breaking down cognition in terms of attentional mechanisms, working memory, and higher-order processing, contributors discuss general models of cognition and personality. Chapter authors build on this foundation as they revisit current theory in such areas as processing effort and general arousal and examine emerging methods in individual differences research, including new data on the role of brain plasticity in cognitive function. The possibility of a unified theory of individual differences in cognitive ability and the extent to which these variables may account for real-world competencies are emphasized, and commentary chapters offer suggestions for further research priorities. Researchers, clinicians, and graduate students in psychology and cognitive sciences, including clinical psychology and neuropsychology, personality and social psychology, neuroscience, and education, will find the Handbook of Individual Differences in Cognition an expert guide to the field as it currently stands and to its agenda for the future.
General Models of Individual Differences in Cognition -- Individual Differences in Cognition: in Search of a General Model of Behaviour Control -- Individual Differences in Cognition: New Methods for Examining the Personality-Cognition Link -- The Relationship Between Intelligence and Pavlovian Temperament Traits: The Role of Gender and Level of Intelligence -- General Models of Individual Differences in Cognition: The Commentaries -- Individual Differences in Cognition from a Neurophysiological Perspective -- Neuroscientific Approaches to the Study of Individual Differences in Cognition and Personality -- Cognitive Neuroscience Approaches to Individual Differences in Working Memory and Executive Control: Conceptual and Methodological Issues -- Emotional Intelligence and Gender: A Neurophysiological Perspective -- Learned Irrelevance Revisited: Pathology-Based Individual Differences, Normal Variation and Neural Correlates -- Post-Soviet Psychology and Individual Differences in Cognition: A Psychophysiological Perspective -- Individual Differences in Cognition from a Neurophysiological Perspective: The Commentaries -- Individual Differences in Attentional Mechanisms -- Psychopathology and Individual Differences in Latent Inhibition: Schizophrenia and Schizotypality -- Attentional Control Theory of Anxiety: Recent Developments -- Task Engagement, Attention, and Executive Control -- Individual Differences in Resource Allocation Policy -- The Relationship of Attention and Intelligence -- Intelligence and Cognitive Control -- Individual Differences in Attention: The Commentaries -- Individual Differences in Working Memory Functioning and Higher-Order Processing -- Trait and State Differences in Working Memory Capacity -- Adrift in the Stream of Thought: The Effects of Mind Wandering on Executive Control and Working Memory Capacity -- The Unique Cognitive Limitation in Subclinical Depression: The Impairment of Mental Model Construction -- Working Memory Capacity and Individual Differences in Higher-Level Cognition -- Motivation Towards Closure and Cognitive Resources: An Individual Differences Approach -- Mood as Information: The Regulatory Role of Personality -- Autobiographical Memory: Individual Differences and Developmental Course -- Individual Differences in Working Memory and Higher-Ordered Processing: The Commentaries -- Conclusion: The State of the Art in Research on Individual Differences in Executive Control and Cognition.
Keywords: Philosophy (General).; Educational psychology; Psychology, clinical; Consciousness; Psychology; Cognitive Psychology; Educational Psychology; Personality and Social Psychology; Clinical Psychology